Pengaruh Model PBL Berbantuan Media Virtual Tehadap Kemampuan Pemecahan Masalah Fisika - Andriyani Hastuti; Hairunnisyah Sahidu; Gunawan Gunawan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
This study aims to determine the effect model of Problem Based Learning (PBL) aided virtual media to the mastery of the concepts of physics students SMK 1 Lingsar Academic Year 2015/2016. This study is a quasi-experimental design with Nonequivalent Control Group Design. The study population all students of class X SMK 1 Lingsar and research sample class X-1 and X MM MM-3 were selected by purposive sampling. Data analysis using polled variance t test. The results showed that the model PBL-aided virtual media influence on students' mastery of concepts of physics. Judging from the average value, penguasaam concepts of physics experimental class is higher than the control class. N-gain first test showed that an increase in the value of the mastery of the concept of the experimental class to the theory and calculation.ÃÂ  N-gain second Test results show that the experimental group was higher than the control class in each sub material unless the material collision